2019
DOI: 10.1097/md.0000000000017654
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Comparing Phacoemulsification Combined with goniosynechialysis to other mainstream procedures in treating patients with angle-closure glaucoma

Abstract: Background:The aim of this meta-analysis is to compare the efficacy and safety of combined phacoemulsification (Phaco) with goniosynechialysis (GSL) to either Phaco or to Phaco combined with trabeculectomy or trabeculectomy alone in patients with angle closure glaucoma (ACG).Methods:Five main electronic databases were searched for the eligible studies. Intraocular pressure (IOP) decrease was set as the primary outcome, while anti-glaucomatous medication decrease, changes of anterior chamber depth (ACD), range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Comparing corneal endothelial counts of the two groups at different postoperative time points revealed that GSL did not increase damage to the corneal endothelium, indicating that phacoemulsification combined with GSL is safe. In line with our findings, White et al [ 13 ] reported that phacoemulsification combined with GSL reduced IOP and the need for IOP-lowering drugs and surgery; in addition, Liu et al [ 14 ] reported that phacoemulsification combined with GSL was the best surgical method for the treatment of angle-closure glaucoma with cataracts. The IOP-lowering ability of this operation was comparable to that of phacoemulsification combined with trabeculectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing corneal endothelial counts of the two groups at different postoperative time points revealed that GSL did not increase damage to the corneal endothelium, indicating that phacoemulsification combined with GSL is safe. In line with our findings, White et al [ 13 ] reported that phacoemulsification combined with GSL reduced IOP and the need for IOP-lowering drugs and surgery; in addition, Liu et al [ 14 ] reported that phacoemulsification combined with GSL was the best surgical method for the treatment of angle-closure glaucoma with cataracts. The IOP-lowering ability of this operation was comparable to that of phacoemulsification combined with trabeculectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Surgical treatment approaches in those patients include phacoemulsification, trabeculectomy, Phaco-trabeculectomy, goniosynechialysis, and Phaco-goniosynechialysis ( 14 ). A meta-analysis of angle-closure glaucoma reported that IOP in the PEGS group decreased significantly more than in Phaco alone group, and there was no statistical difference between PEGS group and Phaco-trabeculectomy/ trabeculectomy group ( 15 ). This is in accordance with our study that Phaco-visco dissection has a satisfactory IOP decrease and a possible improvement of trabecular meshwork function in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Goniosynechiolysis (GSL) is another tool that might be combined with the phacoemulsification procedure, especially when a significant amount of anterior synechiae is still present during intraoperative gonioscopy after the cataract is removed [39]. Combining GSL to phacoemulsification seems to be superior to phacoemulsification alone and comparable to trabeculectomy or phacotrabeculectomy in terms of IOP reduction in chronic angle-closure patients [40].…”
Section: Primary Angle-closure Glaucomamentioning
confidence: 99%